PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP SEMANGAT KERJA GURU PADA SMA NEGERI 3 SIBOLGA - Wendy Susanto Tambunan; Hadijah Sipahutar; Indra Setiawan Hutabarat (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the influence of the work environment and compensation on the work spirit of teachers at SMA Negeri 3 Sibolga. The type of research used in this study is a descriptive quantitative research type, because this research method aims to obtain information by creating a picture or description of what exists or is happening. For this study, the population was 56 (fifty-six) people, the population was taken from all teachers at SMA Negeri 3 Sibolga. Because the population is below 100 people, the author took the entire population to be used as a sample, namely 56 (fifty-six) people. The type of data used in this thesis research is the type of subject data and the source of the data is primary. From the results of the instrument test, valid and reliable results were obtained because all questions contained in variables X1, X2 and Y have a Corrected Item-Total Correlation value of more than 0.300 and a Cronbach's Alpha value of each variable above 0.60, which means that all questions are valid. and reliability. From the classical assumption test, the research data is normally distributed because the histogram graph is bell-shaped, in the P-P Plot graph above, the data distribution can be seen close to the diagonal line and in the multicollinearity test, the tolerance value is ˃ 0.1 and the variance inflation factor (VIF) value <10, so it can be concluded that in the regression model, there is a correlation between independent variables. From the results of the data test, an influence of 71.6% was obtained, this means that what happens to the variation of the dependent variable is 71.6% determined by the independent variable, from the hypothesis test, the results of the calculated t value <t table, so Ha is accepted and H0 is rejected and the results of the F test obtained a calculated F value of 55.599 with a significance level of 0.000 and a calculated F value> F table, which is 24.642> 4.15. Based on this, the hypothesis proposed in this study is accepted. Keywords: Work Environment, Compensation and Work Spirit.